1988
DOI: 10.1515/znc-1988-11-1204
|View full text |Cite
|
Sign up to set email alerts
|

Dimers of Altersolanol A from Alternaria solani

Abstract: Weakly phytotoxic, water-soluble pigments from culture filtrates of the potato early blight organism Alternaria solani have been identified by 1H NMR, UV, mass spectrometric, and acetylation studies as the pair of rotamers represented by structure 1a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…The maximum chemical shift difference between these molecules was 0.04 ppm (in both CD 3 OD and THF-d 8 ). Our analyses led us to conclude that these compounds have identical structures with alterporriols D and E which had been reported by Stoessl and coworkers 6 in 1988 or Suemitsu et al 7 in 1989. However, Stoessl reported that the difference of the d values for C7-OCH 3 between the isomers was 0.12 ppm in methanol-d 4 , which is much larger than what we observed.…”
Section: Axial Stereochemistries Of Alterporriols D (2) and E (3)supporting
confidence: 84%
See 1 more Smart Citation
“…The maximum chemical shift difference between these molecules was 0.04 ppm (in both CD 3 OD and THF-d 8 ). Our analyses led us to conclude that these compounds have identical structures with alterporriols D and E which had been reported by Stoessl and coworkers 6 in 1988 or Suemitsu et al 7 in 1989. However, Stoessl reported that the difference of the d values for C7-OCH 3 between the isomers was 0.12 ppm in methanol-d 4 , which is much larger than what we observed.…”
Section: Axial Stereochemistries Of Alterporriols D (2) and E (3)supporting
confidence: 84%
“…and its relatives by several groups. [1][2][3][4][5] Dimers 2 and 3 were also reported by Stoessl and coworkers 6 and Suemitsu et al 7 independently, and the names alterporriols D and E (2 and 3) were given by Suemitsu et al 7 We also isolated these compounds from Pleospora herbarum, a close relative of the aforementioned fungus. Although our NMR spectral analyses of the dimers suggested the same structures with those of alterporriols D and E, their 1 H NMR data showed considerable difference to those of Suemitsu (max Dd was 0.6 ppm in THF-d 8 ).…”
Section: Introductionsupporting
confidence: 74%
“…[5, 23,24,37] However, their axial chirality has not yet been assigned. Regarding their biaryl chromophoric system, 6 and 7 show close similarity to 2, which also has a 5 monomeric unit but the other monomer is fully conjugated.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of their NMR and mass spectroscopic data and by comparison with the literature data, the remaining compounds were identified as altersolanol A (5), [29][30][31] altersolanol B (6), [30,31] altersolanol C (7), [32] alterporriol D (8), [33][34][35] alterporriol E (9), [32][33][34][35] macrosporin (10), [30] and 6-O-methylalaternin (11). [26] Compounds 1-11 were examined for their effects on the growth of the murine lymphoma L5178Y cell line through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The fungal extract caused a significant growth inhibition of the murine lymphoma cell line L5178Y, which prompted us to investigate the compounds produced by this endophyte. [26,[29][30][31][32][33][34][35] The structure elucidation of the new compounds as well as results of cytotoxic and antibacterial bioassays are reported. produce a broad spectrum of polyketide secondary metabolites with different bioactivities, such as the antimicrobial stemphyltoxin I-IV, [22] the phytotoxic chromone glucosides stemphyloxin I and II, [23,24] the cytotoxic altersolanol A, B, and C, [25,26] as well as the protein kinase inhibitors alterporriol G and H. [25][26][27] In our previous study, the first naturally occurring trimeric anthraquinone derivatives, stemphylanthranol A and B, were isolated from S. globuliferum.…”
Section: Introductionmentioning
confidence: 99%